Akhlaq Education Conception of ibn Miskawaih and al-Ghazali and Its Relevancy to The Philosophy of Muhammadiyah Pesantren - Kuswandi, Iwan (Proceeding of International Conference on Islamic Education (ICIED); Vol 4 No 1 (2019): Proceeding of International Conference on Islamic Education (ICIED), 2019)
Studies of Ibn Miskawaih and al-Ghazali thought are at all times thought-provoking. Even though both of them are figures from the same religion, their concepts have similarities and differences which stimulate lengthy discussion. This paper examined how the concept of moral according to Ibn Miskawaih and al-Ghazali and analyzed how relevant it is to the philosophy of Muhammadiyah pesantren. Ibn Miskawaih was a more open figure to Western philosophical thinking. It made him more rational than al-Ghazali. Al-Ghazali, the pioneer of Sunni Sufism, repeatedly criticized Western philosophical thinking as his approach was mystical tradition. Rational ethics of Ibn Miskawaih are considered relevant to modernism today; while Al-Ghazali's mystical ethics has become the major influence and earned good reputation among Muslims, especially within the pesantren community. Thus, it was reasonable that Ibn Miskawaih was given the title of the Third Teacher ( al-Muallim al-Tsalits ) and al-Ghazali was given the title of hujjah al-Islam. The conception of these two figures has special relevance to the philosophy of Muhammadiyah pesantren across Indonesia. Ibn Miskawaih conception is considered relevant to the efforts of integrating general knowledge and religion, which is carried out by the Muhammadiyah pesantren. On the other hand, the conception of al-Ghazali's which originated from the Qur'an and the Sunnah is very relevant to the Islamic spirit of Muhammadiyah. It means that Ibn Miskawaih conception is epistemologically in line with the integration of education in the Muhammadiyah pesantren, while al-Ghazali's conception is considered ontologically relevant, because it prioritized the reference of the Qur'an and the Sunnah. The axiological value of education in the Muhammadiyah pesantren lies in logical reason, the Qur'an and the Sunnah.